DISEASES OF THE DIGESTIVE SYSTEM AND THEIR RISK FACTORS (World Bulletin of Public Health, 2024)
This article provides information about diseases of the digestive system , the main causes of disorders of the digestive process, and the actions to be taken to prevent diseases of the digestive system